Effectiveness of Public Health Campaigns in Reducing Oral Cancer Incidence in Urban Maharashtra - Eric Kwasi Elliason; Atul Khajuria; Stephen Monday; J. Samuel Kamanda (International Journal of Evidence Based Nursing And Practices, 2025)
Introduction: Oral cancer is a major public health problem in urban Maharashtra which can be attributed to high consumption of tobacco, late presentation, and poor awareness. To tackle these issues, public health campaigns have been established to encourage early diagnosis, lifestyle modification, and availability of health resources. This study assesses the impact of these campaigns on the reduction of oral cancer incidence and awareness level in the population. Methods: This is a mixed-methods study, incorporating both a quantitative analysis of oral cancer incidence trends. It combined a quantitative component (the quantitative analysis of secondary data from hospital records and public health databases) and a qualitative approach (interviews with health professionals, policymakers, and affected individuals). The study also evaluated awareness campaign reach, content, and impact via surveys and observational analysis. Results: The results show that targeted public health campaigns have resulted in improved knowledge, increased utilization of screening for asymptomatic individuals and a reduction in high-risk behaviors like tobacco use. Pre-andpost-intervention comparative analysis indicated a reduction of oral cancer incidence being witnessed in areas in which a vigorous campaign was plausible. But there are still disparities in access to preventive care, especially for lower socioeconomic groups. Qualitative findings highlight the role of culturally appropriate messaging and community engagement in the implementation ofpublic health technology. Conclusion: Public health campaigns have been pivotal in reducing the burden of oral cancer in urban Maharashtra, but persistent action is essential to address the persisting discrepancies. Large scale approaches, such as boosting of school-based programs, utilizing digital media, and including screening into primary healthcare services could augment the sustained impact of these interventions. Policymakers need to employ targeted strategies to achieve equitable access to preventive care and early detection to further reduce oral cancer incidence.
Keywords: Maharashtra; Oral Cancer; cancer prevention; early detection; health awareness; health behavior change; public health campaigns; tobacco cessation